Manajemen Pendidikan Karakter Sebagai Konten Mengejawantahkan Ajaran dan Nilai-nilai Luhur Pendidikan - I Made Ariasa Giri (Purwadita : Jurnal Agama dan Budaya, 2019)
Characters have a proper urgency to be given maximum emphasis in the educational world. Character Education management is a strategy that is applied in the development of character education that is organized with the desire and intent to fulfill the teachings and values of noble to realize the social mission of the school through activities Management. Learning in schools, the process of transforming sublime values through character education. Character education is a key word of the transformation of noble values in school. The objective of character education Management can strengthen and develop the values of life that are considered important and necessary so that they become the personality of the typical student ownership as the values are developed, correcting Conduct of learners that do not correspond with the values developed by the school. and establish harmonious connections with families and communities in the role of shared character responsibilities.